1967
DOI: 10.2307/3015
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of Reproduction in Some Species of Ceriodaphnia (Crustacea: Cladocera)

Abstract: All rights reserved INFO RM ATIO N TO ALL USERSThe quality of this reproduction is dependent upon the quality of the copy submitted.In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if material had to be removed, a note will indicate the deletion. Relationship between egg number and body length. ^i.Relationship of egg volume to body length. 36.Egg number, body length, temperature, and chlorophyll. 41»The shape of Ceriodaphnia eggs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…1). Daphnia magna is sensitive to crowding and environmental change, while D, puler is tolerant (Smith 1963, ~utchinson 1967, Burgis 1967. In a similar situation D. puler eliminated C. megalops from WEUP Pond (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…1). Daphnia magna is sensitive to crowding and environmental change, while D, puler is tolerant (Smith 1963, ~utchinson 1967, Burgis 1967. In a similar situation D. puler eliminated C. megalops from WEUP Pond (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, the feeding strategy of C. laticaudata is known to differ from that of D. puler (Hutchinson 1967). Neither species appears to compete with D. pulex and all are capable of living under adverse environmental conditions (Hutchinson 1967, Burgis 1967. The gradual increase during the winter in the size of the D. pulex and D. m a w populations and the occurrence in these species of a large number of parthenogenetic broods suggested that their reproductive efforts were directed toward the production of subitaneous eggs (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…For both egg types, the eg^ of C. megalops are approximately twice the volume of the eggs of C. pulchella (Tables 1 and 4). Burgis (1967) found that the volume of a clutch of parthenogenetic eggs increased directly to body length in both species. Such a relationship does not apply to their resting eggs; the volume of a resting egg being independent of maternal body length in each species.…”
Section: Discussionmentioning
confidence: 96%
“…Synopsis of data given by Burgis (1967) for Ceriodaphnia megalops and Ceriodaphnia pulchella. All data refer to parthenogenetic females (Burgis, 1967). / = egg length; w = egg width.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted in some reports that the temperatures within the range of 15.0-25.0°C positively affect the growth and reproduction in C. quadrangula [9,13,14,28]. According to some reports [22] temperatures within the range of 16.0-20.0°C are optimal; according to others [24] the opti mal range is 17.0-23.0°C.…”
Section: Discussionmentioning
confidence: 99%